THE RELEVANCE OF ATTENTION TO L2 FORM IN COMMUNICATIVE CLASSROOM CONTEXTS - García Mayo, María del Pilar (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This paper presents an overview of the rationale for the return to the relevance of L2 form in the communicative language classroom, and provides ideas about how to draw learners’ attention to formal aspects of language within the backdrop of a task-based approach to language teaching. The paper offers an updated review of the approach to grammar instruction known as Focus-on-Form (FonF), an instructional option that calls for an integration of grammar and communication in non-native language teaching, and provides research-informed insights that might be of use for the classroom practitioner. Several avenues for research on FonF are also presented, considering new instructional settings and the access to computer-mediated communication. A call for the strengthening of the link between second language acquisition (SLA) research findings and language pedagogy is made as a way to contribute to more ecologically valid classroom research and pedagogy. Resumen Este trabajo se centra en los motivos que han llevado a volver a poner de relieve la pertinencia de la forma lingüística en la enseñanza de lenguas dentro de un enfoque comunicativo y proporciona ideas de cómo hacer que los alumnos dirijan su atención hacia esos aspectos formales dentro del marco de la enseñanza/aprendizaje por tareas. El trabajo proporciona una revisión actualizada de la aproximación didáctica conocida como ‘atención a la forma’, una opción pedagógica que busca integrar la gramática y la comunicación en la enseñanza de lenguas no maternas, y proporciona ideas que provienen de las investigaciones realizadas y que pueden ser útiles para el profesorado. También se identifican varias líneas de investigación sobre la atención a la forma teniendo en cuenta nuevos escenarios de enseñanza y el acceso a la comunicación a través del ordenador. Se aboga por reforzar la interrelación entre los resultados de las investigaciones sobre la adquisición de segundas lenguas y la práctica docente para beneficio de ambos campos.